The attitude towards the people of other nations through the prism of the attitude to yourself - Konyukh, Olha (Journal of Education Culture and Society, 2020)
The article presents the results of theoretical analysis and empirical investigation of the relationship between self-attitude and attitude towards other people, including representatives of other nationalities. Self-attitude is viwed as a stable, emotionally charged of your own self. The interdependance of self-attitude indicators with the features of ethnic tolerance and the character of other individuals' attitude in complicated situations has been researched. Individuals with different self-image are shown to perceive their opponents just as they perceive their own personality. Perception and emotional attitude both to their own ethnic group and other ethnicities is closely related to the attitude of the individual to himself, and common factors in predisposition to criticism and condescension towards themselves and others.